Changing trends in uterine rupture audit, from the Institute of obstetrics and gynecology, modern government maternity hospital, Osmania medical college - Devabhaktuni, Pratibha; Allani, Padmaja; F., Maheen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Between January 2001 to September 2003, 46,171 deliveries were recorded, the number of caesarean deliveries during this period of two years and nine months were 16,182 (35.04%). Methods: An Audit from the Institute of obstetrics and gynecology, of uterine ruptures. Results: Total 81 cases of uterine rupture were managed at the Institute. Total number of scar ruptures managed were, 48/81 uterine ruptures. Five women had previous classical upper segment caesarean, and in previous lower segment caesarean section (LSCS), there were 43 cases of rupture uterus. In two cases following forceps delivery, traumatic uterine ruptures were recorded. Spontaneous ruptures were 31 during the study period. Bladder rupture occurred in 13 cases, 16.04% of uterine ruptures. The fetal outcome in uterine ruptures 81 cases, live births were 19-23.45%. The number of vaginal births after caesarean section were 261, 215, 186 in the years 2001, 2002 and 2003 at the Institute of obstetrics and gynecology. The number of scar ruptures were 7/261, 9/215, 2/186 in the respective years. Hysterectomy was done in 43/81=53.08%. Rent repair of the uterine rupture was done in 38/81. Conclusions: An Audit from the Institute of obstetrics and gynecology, of uterine ruptures has provided the following data that gives an insight into the practice of obstetrics during the decade 2000 to 2010 in the teaching Institute. Caesarean deliveries accounted for 35.04% of the total deliveries. Repeat caesarean sections were 7105, 43.9%. The number of vaginal births after caesarean section (VBAC) were 662. Scar ruptures in VBAC were 18 /662-2.71%. The maternal mortality in MGMH study was 3/81 uterine ruptures-3.7%. Scar ruptures constituted, 48/81-59.25% of uterine ruptures. Trial of labor after caesarean (TOLAC) and VBAC are practiced in the teaching Institute.